เปิดประเด็น: การพัฒนาผู้เรียนด้วยการประเมินเพื่อการเรียนรู้ - แก้วดี สกลรัชต์ (Journal of Education Studies, Chulalongkorn University, 2018)
Abstract Assessment for learning (AFL) is a teaching and learning approach which provides an opportunity for learners to involve in their learning processes by giving feedback during their engagement in learning activities. Through the AFL approach, learners know what they understand and what they do not understand, and how to develop and improve their learning to achieve expected learning outcomes. The strategies of AFL consist of questioning, feedback, peer assessment, and self-assessment. AFL approach could help to create a student-centered classroom and positive learning environment. Therefore, it enhances the learning process of learners and develops analytical thinking, critical thinking, and learning responsibility for learners.